Optimization of lotion formulation 70 % ethanol extract longan leaves (dimocarpus logan l.) - Rony Setianto; Atia Fitriyawati; Belinda Arbitya Dewi (Journal of Midwifery and Nursing, 2025)
Longan (Dimocarpus longan L.) is a plant from Southeast Asia. One of the health benefits of the longan plant is that it can improve skin health. The aim of the research is optimization in selecting the formulation of the lotion dosage form from 70% ethanol extract from longan leaves. Making longan leaf extract by maceration. Three different concentration formulas of emulsifier span 80 and tween 80 are used to make the lotion. For four weeks, the performance of the lotion was tested organoleptically, in terms of homogeneity, acidity/pH, viscosity, spreadability and specific gravity. Research findings on longan leaf extract can be used as a lotion formulation. FII lotion is the best preparation and is quite stable. The conclusion of this research is that 70% ethanol extract of longan leaves can be made into a stable lotion preparation at varying concentrations of Span 80 and Tween 80 emulsifiers. The best formulation is formulation II.